MOLECULAR CHARACTERIZATION AND MYCOPARASITIC APTITUDE OF INDIGENOUS BIOCONTROL AGENT TRICHODERMA HARZIANUM - G. Mustafa; S. Anwar; F. A. Joyia; M. B. Hayat; M. A. Zia; Ghazala3and M. S. Khan (Journal of Animal and Plant Sciences, 2020)
Biocontrol agents are always desirous owing to health-conscious attitude and deleterious effects of the chemicals used to control fungal pathogens. In this study, isolates of a biocontrol agent (Trichoderma harzianum) were purified while growing on Potato Dextrose Agar (PDA) containing one ml of chloramphenicol (1M rexaphenicol). DNA based identification of these fungal isolates was carried out by targeting internal transcribed spacer (ITS) region which is one of the most authenticated markers in molecular systematics. These isolates were also assessed for glucanase production ability, a key indicator of mycoparasitism. Extracellular β-1,3-glucanase enzyme was purified by gel filtration chromatography using sephadex column G-75. The purified glucanase appeared as a single band on SDS-PAGE, exhibiting molecular weight of approximately 70 kDa. Further, purified enzyme was also characterized for various optima in order to appraise its activity. The enzyme was found to be stable and active at a broad range of pH (5-8) and depicted maximum activity at slightly acidic pH of 5.5. It showed maximum activity at 25oC, however, remained remarkably active even at 50oC revealing its thermo-tolerance and suitability for industrial usage. Hence, these Trichoderma isolates can not only be used to produce stable glucanase enzyme for industrial applications but can also be used as a proficient biocontrol agent for fungal pathogens.
Keywords: Trichoderma harzianum; ITS; β-1; 3-glucanase; purification; characterization; SDS-PAGE